An Implementation of Catmap-Rijndael (AES) Algorithm For Image Security (Case Study on A Software For Making Students Card At Universitas Jenderal Soedirman) - Bangun Wijayanto; Retantyo Wardoyo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2011)
Abstract— The function of image encryption is to transform known have that meaning to images that cannot be read or irregular images in order to security. Storing the image data in local computer system will bring some risks on the image security.The aim of this research is to construct an image encryption system based on Catmap-Rijndael algorithm. The system is implemented on a software form making students card at Universitas Jenderal Soedirman. The result shows that the combination of Catmap-Rijndael algorithm on bitmap image 200x200 pixel by using 3 times repetition of the Catmap algorithm (with parameter a=1 and b=1) can overcome the problem of textured of the object that caused by base colour on the image and uniform histogram of the encrypted image in short time process.Keywords— Rijndael, AES, Catmap, image security, students card.